2022
DOI: 10.1038/s41386-022-01359-5
|View full text |Cite|
|
Sign up to set email alerts
|

Association of day-of-injury plasma glial fibrillary acidic protein concentration and six-month posttraumatic stress disorder in patients with mild traumatic brain injury

Abstract: Several proteins have proven useful as blood-based biomarkers to assist in evaluation and management of traumatic brain injury (TBI). The objective of this study was to determine whether two day-of-injury blood-based biomarkers are predictive of posttraumatic stress disorder (PTSD). We used data from 1143 individuals with mild TBI (mTBI; defined as admission Glasgow Coma Scale [GCS] score 13–15) enrolled in TRACK-TBI, a prospective longitudinal study of level 1 trauma center patients. Plasma glial fibrillary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, it has also been reported that levels of GFAP are elevated in individuals with PTSD. However, the findings are not consistent across studies, and more research is needed to establish a clear and reliable connection [15,16]. To investigate this issue, we examined GFAP levels in a pilot cohort who were diagnosed with PTSD and taking SSRIs and determined GFAP levels in individuals who were prescribed an SSRI irrespective of their PTSD diagnosis.…”
Section: Gfap Levels Across Control and Ptsd Individuals And Individu...mentioning
confidence: 99%
“…Moreover, it has also been reported that levels of GFAP are elevated in individuals with PTSD. However, the findings are not consistent across studies, and more research is needed to establish a clear and reliable connection [15,16]. To investigate this issue, we examined GFAP levels in a pilot cohort who were diagnosed with PTSD and taking SSRIs and determined GFAP levels in individuals who were prescribed an SSRI irrespective of their PTSD diagnosis.…”
Section: Gfap Levels Across Control and Ptsd Individuals And Individu...mentioning
confidence: 99%
“…Risks for post-traumatic stress disorder (PTSD), depression, and other mental diseases increase dramatically after a TBI (Barnes et al, 2018 ; Roy et al, 2019 ; Stein et al, 2019 ; Kulbe et al, 2022 ). Patients dealing with TBIs' long-term effects are often at the risk of developing cognitive impairment (CI) or post-concussion syndrome (PCS) (Mehrolhassani et al, 2020 ).…”
Section: Evs As Potential Predictors Of Functional Outcomes In Tbimentioning
confidence: 99%
“… 7 , 8 In fact, several studies have shown that GFAP concentration is related to prognostic factors of TBI patients such as GCS, lactate, Acute Physiology and Chronic Health Evaluation II (APACHE II) score, Rotterdam score, SAPS II score. 9 , 10 During the treatment process of TBI patients, GFAP levels and some prognostic factors such as GCS, lactate, APACHE II score, Rotterdam score, and SAPS II score all change regularly. Furthermore, these indicators indirectly reflect severity or better improvement.…”
Section: Introductionmentioning
confidence: 99%